Design and analysis of multi-cavity traditional and h-branching runners for plastic injection mold - Mohd. Rizwan, Hamsin; Azuddin, Mamat; Aznijar, Ahmad-Yazid (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/